Acute Exercise and Insulin Sensitivity in Boys: A Time-Course Study - Cockcroft, Emma J.; Williams, Craig A.; Weaver, Hayley; O'Connor, Amy; Jackman, Sarah R.; Armstrong, Neil; Barker, Alan R. (International Journal of Sports Medicine, 2017)
This study examined the time course of adaptions in insulin sensitivity (IS) in adolescent boys after acute high-intensity interval exercise (HIIE) and moderate-intensity exercise (MIE). Eight boys (15.1±0.4 y) completed three 3-day experimental trials in a randomised order: 1) 8×1 min cycling at 90% peak power with 75 s recovery (HIIE); 2) cycling at 90% of gas exchange threshold for a duration to match work during HIIE (MIE); and 3) rest (CON). Plasma [glucose] and [insulin] were measured before (PRE-Ex), 24 and 48 h post (24 h-POST, 48 h-POST) in a fasted state, and 40 min (POST-Ex) and 24 h (24 h-POST) post in response to an oral glucose tolerance test (OGTT). IS was estimated using the Cederholm (OGTT) and HOMA (fasted) indices. There was no change to HOMA at 24 h or 48 h-POST (all P>0.05). IS from the OGTT was higher POST-EX for HIIE compared to CON (17.4%, P=0.010, ES=1.06), and a non-significant increase in IS after MIE compared to CON (9.0%, P=0.14, ES=0.59). At 24 h-POST, IS was higher following both HIIE and MIE compared to CON (HIIE: P=0.019, 13.2%, ES=0.88; MIE: 9.7%, P=0.024, ES=0.65). In conclusion, improvements to IS after a single bout of HIIE and MIE persist up to 24 h after exercise when assessed by OGTT.